Genetic Variants of MICB and PLCE1 and Associations with Non-Severe Dengue - Simmons, Cameron (2018)
BACKGROUND: A recent genome-wide association study (GWAS) identified susceptibility loci for dengue shock syndrome (DSS) at MICB rs3132468 and PLCE1 rs3740360. The aim of this study was to define the extent to which MICB (rs3132468) and PLCE1 (rs3740360) were associated with less severe clinical phenotypes of pediatric and adult dengue. METHODS: 3961 laboratory-confirmed dengue cases and 5968 controls were genotyped at MICB rs3132468 and PLCE1 rs3740360. Per-allele odds ratios (OR) with 95% confidence intervals (CI) were calculated for each patient cohort. Pooled analyses were performed for adults and paediatrics respectively using a fixed effects model. RESULTS: Pooled analysis of the paediatric and adult cohorts indicated a significant association between MICB rs3132468 and dengue cases without shock (OR = 1.15; 95%CI: 1.07 - 1.24; P = 0.0012). Similarly, pooled analysis of pediatric and adult cohorts indicated a significant association between dengue cases without shock and PLCE1 rs3740360 (OR = 0.92; 95%CI: 0.85 - 0.99; P = 0.018). We also note significant association between both SNPs (OR = 1.48; P = 0.0075 for MICB rs3132468 and OR = 0.75, P = 0.041 for PLCE1 rs3740360) and dengue in infants. DISCUSSION: This study confirms that the MICB rs3132468 and PLCE1 rs3740360 risk genotypes are not only associated with DSS, but are also associated with less severe clinical phenotypes of dengue, as well as with dengue in infants. These findings have implications for our understanding of dengue pathogenesis.